Liquid Phase Epitaxy growth and luminescence of Terbium-doped Gd3Ga5O12 crystalline layers - Baillard Amandine; Douissard Paul-Antoine; Loiko Pavel; Wollesen Laura; Martin Thierry; Mathieu Eric; Ziegler Eric; Brasse Gurvan; Camy Patrice (EPJ Web of Conferences, 2023)
Tb3+-doped single-crystalline Gd3Ga5O12 layers are grown by Liquid Phase Epitaxy on (111)-oriented undoped substrates, and their structure, composition, morphology and photo- and radioluminescence are studied. Layers doped with 6 at.% Tb3+ with a thickness up to 20 μm appear promising for single crystal film scintillators with a sub-μm spatial resolution and waveguide lasers as they exhibit good quality, uniform distribution of Tb3+ ions, optimized light output (~50% of that for Ce:YAG), weak concentration quenching of luminescence and low afterglow for a 15 bit dynamic range.